Method for manufacturing oxidized carbon, method for manufacturing carbon mixture, and method for manufacturing electrode
By strong oxidation treatment of almost non-porous carbon materials, it expands in a gel shape when under pressure, solving the problem of space-time generation of electrodes in dry manufacturing, and achieving an improvement in electrode density and battery energy density.
Patent Information
- Application Number
- JP2023156349
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-03
AI Technical Summary
During the manufacturing process of battery electrodes, it is difficult to effectively suppress the generation of cavity in the electrodes directly by applying pressure through dry process, resulting in the electrode density not meeting expectations, affecting the energy density and electrochemical performance of the battery.
Almost non-porous carbon material is selected as the raw material, and by controlling its average primary particle diameter and grain properties, it is subjected to strong oxidation treatment to expand in a gel shape when under pressure, thereby suppressing the generation of cavity when the electrode is manufactured by dry method and improving the electrode density.
Through this method, the generation of cavity in the electrode is successfully suppressed, significantly improving the electrode density and the energy density of the battery, while improving the electrochemical performance.
Smart Images

Figure 2025047704000004 
Figure 2025047704000005 
Figure 2025047704000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing an oxidized carbon having a property of turning into a paste when subjected to pressure, which is to be used as a conductive agent in an electrode of an electricity storage device, and a method for producing a carbon mixture containing the oxidized carbon. The present invention also relates to a method for producing an electrode of an electricity storage device using the oxidized carbon or the carbon mixture. [Background technology]
[0002] Power storage devices such as secondary batteries, electric double layer capacitors, redox capacitors, and hybrid capacitors are devices whose applications are being considered widely as power sources for information devices such as mobile phones and notebook computers, motor drive power sources for low-pollution vehicles such as electric vehicles and hybrid vehicles, and energy regeneration systems. However, in order to meet the demand for higher performance and smaller size of these power storage devices, there is a demand for improving the energy density.
[0003] In these power storage devices, electrode active materials that exhibit capacity through a faradaic reaction involving the transfer of electrons with ions in an electrolyte (including an electrolytic solution) or a non-faradaic reaction not involving the transfer of electrons are used for energy storage. These active materials are generally used in the form of a composite material with a conductive agent. As the conductive agent, conductive carbons such as carbon black, natural graphite, artificial graphite, and carbon nanotubes are usually used. These conductive carbons are used in combination with active materials with low conductivity to impart conductivity to the composite material, but they also act as a matrix that absorbs volume changes associated with the reaction of the active material, and also play a role in ensuring an electronic conduction path even if the active material is mechanically damaged.
[0004] By the way, these composite materials of active material and conductive carbon are generally manufactured by a method of mixing active material particles with conductive carbon. Since conductive carbon does not basically contribute to improving the energy density of an electricity storage device, in order to obtain an electricity storage device with a high energy density, it is necessary to reduce the amount of conductive carbon per unit volume and increase the amount of active material. Therefore, studies have been conducted to increase the amount of active material per unit volume by improving the dispersibility of conductive carbon or reducing the structure of conductive carbon to reduce the distance between active material particles, but it is difficult to efficiently insert the above-mentioned conductive carbon between active material particles, and therefore it is difficult to reduce the distance between active material particles to increase the amount of active material per unit volume.
[0005] In response to this problem, the applicant has proposed to use oxidized carbon, which can be obtained by subjecting a conductive carbon raw material to a strong oxidation treatment and has the property of spreading into a paste-like shape when subjected to pressure, as a conductive agent for electrodes of electricity storage devices (for example, Patent Document 1 (WO2015 / 133586), Patent Document 2 (JP 2016-096125 A), Patent Document 3 (JP 2022-035788 A)). Here, "paste-like" means a state in which the grain boundaries of primary carbon particles are not observed in an SEM photograph taken at a magnification of 25,000 times, and non-particulate amorphous carbon is connected.
[0006] Even when pressure is applied to conductive carbon such as carbon black, natural graphite, and carbon nanotubes, which are used as conductive agents in the electrodes of conventional power storage devices, the particle shape of the carbon is maintained. However, when these conductive carbons are subjected to an oxidation treatment, the surface of the particles is oxidized, and hydroxyl groups, carboxyl groups, carbonyl groups, ether bonds, etc. are introduced into the carbon, and the conjugated double bonds of the carbon are oxidized to form carbon single bonds, and carbon-carbon bonds are partially broken. By further increasing the intensity of the oxidation treatment, it is possible to obtain oxidized carbon that has the property of spreading like a paste when subjected to pressure.
[0007] The oxidation-treated carbon, which has the property of spreading like a paste when subjected to this pressure, has the characteristic that it easily adheres to the surface of the electrode active material particles, and when pressure is applied, it is compressed together and spreads like a paste, and is difficult to break apart. Therefore, when this oxidation-treated carbon and the electrode active material particles are mixed to obtain a mixture for an electrode of an electricity storage device, the oxidation-treated carbon adheres to the surface of the active material particles during the mixing process, covering the surface, and improving the dispersibility of the active material particles. If the pressure applied to the oxidation-treated carbon during the production of the mixture is large, at least a part of the oxidation-treated carbon spreads like a paste and partially covers the surface of the active material particles. Then, when pressure is applied to the mixture during the process of producing an electrode for an electricity storage device, the oxidation-treated carbon further spreads like a paste, covering the surface of the electrode active material particles, densifying them and the active material particles approach each other. Therefore, the amount of electrode active material per unit volume in the electrode increases, the electrode density increases, and the energy density of the electricity storage device increases.
[0008] Patent Document 1 shows that when conductive carbon having voids such as porous carbon powder, Ketjen Black, carbon nanofibers, and carbon nanotubes is used as a carbon raw material and oxidized, oxidized carbon having a property of spreading like a paste when pressure is applied can be easily obtained, and a method of using a slurry containing this oxidized carbon for manufacturing an electrode is also shown. Figure 2 of this document shows the relationship between the electrode density and the content of the hydrophilic portion in the oxidized carbon obtained from an experiment in which oxidized carbon obtained by subjecting Ketjen Black to oxidation treatments of different strengths, particles of LiFePO4 as an electrode active material, polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent are thoroughly kneaded to form a slurry, which is then applied to an aluminum foil, dried, and then rolled to obtain an electrode. The meaning of the "hydrophilic portion" of the oxidized carbon and the method of calculating the content of the hydrophilic portion will be described later.
[0009] 2 of Patent Document 1 shows that when the intensity of the oxidation treatment is increased so that the content of the hydrophilic portion exceeds 8 mass% of the entire oxidized carbon, the density of the electrode manufactured using the obtained oxidized carbon begins to increase, when the content of the hydrophilic portion exceeds 9 mass% of the entire oxidized carbon, the electrode density begins to increase rapidly, and when the content of the hydrophilic portion exceeds 10 mass% of the entire oxidized carbon, an extremely high electrode density is obtained. This increase in electrode density corresponds to the fact that as the intensity of the oxidation treatment is increased, the oxidized carbon is given the property of spreading like a paste when pressure is applied.
[0010] Patent Document 2 discloses a method of dry-mixing the oxidized carbon obtained by subjecting the conductive carbon having the above-mentioned voids to an oxidation treatment, which has the property of spreading like a paste when subjected to pressure, with another conductive carbon having a higher conductivity than that of the oxidized carbon, to obtain a carbon mixture in which at least a part of the oxidized carbon is converted into a paste and adheres to the surface of the other conductive carbon, and also discloses a method of using a slurry containing this carbon mixture for the manufacture of electrodes. In Examples 10 and 11 of this document, a carbon mixture is obtained by dry-mixing the oxidized carbon obtained by subjecting Ketjen black to an oxidation treatment, which has the property of spreading like a paste when subjected to pressure, with acetylene black as another conductive carbon, and then mixing this carbon mixture with LiNi as an electrode active material. 0.5 Mn 0.3 Co 0.2 It has been shown that when O2 particles, polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent are thoroughly mixed to form a slurry, and this slurry is applied to an aluminum foil, dried, and then rolled to obtain an electrode, a high electrode density can be obtained, and the DC internal resistance of a lithium ion secondary battery equipped with this electrode is lower than the DC internal resistance of a lithium ion secondary battery equipped with an electrode formed by separately using the above-mentioned oxidized carbon and acetylene black instead of the above-mentioned carbon mixture.
[0011] Patent Document 3 discloses a method of heat-treating the oxidized carbon or carbon mixture containing the oxidized carbon, which has the property of spreading like a paste when subjected to pressure and is obtained by subjecting the conductive carbon having the above-mentioned voids to an oxidation treatment, in a vacuum or in a non-oxidizing atmosphere, thereby reducing the amount of CO2 generated from the oxidized carbon or carbon mixture after the heat treatment in the range of 25 to 200°C compared to the amount of CO2 generated from the oxidized carbon or carbon mixture before the heat treatment in the range of 25 to 200°C. It also discloses a method of using a slurry containing the oxidized carbon or carbon mixture after the heat treatment for the manufacture of an electrode. In Examples 1 to 4 of this document, a carbon mixture is obtained by dry-mixing the oxidized carbon obtained by subjecting Ketjen black to an oxidation treatment and which has the property of spreading like a paste when subjected to pressure with acetylene black as another conductive carbon, and the carbon mixture is heat-treated at a temperature of 200 to 900°C in a nitrogen atmosphere electric furnace, and then the obtained carbon mixture is mixed with LiNi as an electrode active material. 0.5 Mn 0.3 Co 0.2 It has been shown that when O2 particles, polyvinylidene fluoride as a binder, and N-methylpyrrolidone as a solvent are thoroughly mixed to form a slurry, and this slurry is then applied to aluminum foil, dried, and then rolled to obtain an electrode, the charge-discharge cycle stability of an electricity storage device equipped with this electrode when a high voltage is applied is improved. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] WO2015 / 133586 [Patent Document 2] JP 2016-096125 A [Patent Document 3] Patent Publication No. 2022-035788 [Non-patent literature]
[0013] [Non-Patent Document 1] Ore Geology Reviews 70(2015)80-95 Summary of the Invention [Problem to be solved by the invention]
[0014] As described above, Patent Documents 1 to 3 disclose a method in which electrode active material particles and an oxidized carbon or a carbon mixture containing the oxidized carbon, which has a property of changing into a paste-like state when subjected to pressure as a conductive agent, are kneaded with a solvent to form a slurry, and pressure is applied to the slurry after drying. However, a method in which pressure is applied directly to the electrode mixture containing electrode active material particles and an oxidized carbon or a carbon mixture as a conductive agent, without the slurry formation process after the electrode mixture is obtained by dry mixing, is excellent as a method for obtaining an electrode for an electricity storage device simply and inexpensively. In addition, in recent years, studies on all-solid-state batteries have been progressing in order to meet the demands for high energy density, high output density, high safety, and long life, and a method of applying pressure directly to the electrode mixture obtained by dry mixing is used in the manufacture of electrodes for all-solid-state batteries. Hereinafter, the method of applying pressure directly to the electrode mixture, without the slurry formation process after the electrode mixture is obtained by dry mixing, is referred to as a "dry process". In addition, the term "dry press" means the pressure application process in the dry process.
[0015] The oxidation-treated carbon derived from Ketjen Black shown in Patent Documents 1 to 3 has been used in the form of a slurry up to now, but the property of this oxidation-treated carbon, that is, that it easily adheres to the surface of electrode active material particles, and when pressure is applied, it is compressed together and spreads in a paste-like form, and is not easily broken apart, is considered to be suitable for a method of manufacturing an electrode by a dry process. Therefore, an experiment was conducted to form an electrode by a dry process using this oxidation-treated carbon derived from Ketjen Black and an electrode active material, and to measure the electrode density, but the expected improvement in electrode density was not obtained. In addition, when the cross section of the obtained electrode was observed, it was found that many voids existed in the electrode, and that these voids hindered the improvement of the electrode density. The reason why voids occur in the electrode is not clear at this time, but the fact that the electrode density does not improve means that the amount of electrode active material per unit volume in the electrode cannot be increased, and therefore should be improved. In addition, in an electrode for an all-solid-state battery, electrode active material particles, a conductive agent, and solid electrolyte particles for forming an ion conduction path between the electrolyte layer of the battery and the electrode active material particles are used for the electrode, and the battery characteristics are affected by the contact state between these. If the electrode density is not improved, the travel distance of ions responsible for the exchange of electrons with the electrode active material particles may become long, resulting in the generation of a resistance component.
[0016] Therefore, an object of the present invention is to provide a method for producing oxidized carbon that has the property of turning into a paste when subjected to pressure, and is to be used as a conductive agent in the electrodes of an electricity storage device, and that can suppress the occurrence of voids inside the electrodes of an electricity storage device produced via a dry process, thereby increasing electrode density. [Means for solving the problem]
[0017] The inventors selected carbon with few pores, which had not been confirmed to have sufficient performance in terms of its difficulty in oxidation, as a carbon raw material, and examined the difficulty of oxidation until it was given the property of turning into a paste when subjected to pressure. As a result, it was found that even carbon with few pores can be oxidized to the point where it is given the property of turning into a paste when subjected to pressure with the same oxidation treatment strength as that applied to Ketjen Black, so long as it has a small average primary particle size and low crystallinity. Furthermore, it was found that when the obtained oxidized carbon is used to create an electrode for an electricity storage device by a dry process, the generation of voids in the electrode is suppressed, and a high electrode density can be obtained.
[0018] Therefore, the present invention is first a method for producing oxidized carbon to be used as a conductive agent in an electrode of an electricity storage device, comprising the steps of: The oxidation step is to obtain oxidized carbon that has the property of turning into a paste when subjected to pressure by subjecting a conductive carbon raw material to an oxidation treatment. Including, The carbon raw material satisfies the following conditions i), ii) and iii). i) Internal specific surface area is 30m 2 / g or less, ii) the average primary particle size is 35 nm or less; iii) the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum is 1.00 or less; The present invention relates to a method for producing an oxidation-treated carbon, which is characterized in that the carbon satisfies all of the above requirements.
[0019] Regarding condition i), the value of the internal specific surface area of the carbon raw material is calculated by subtracting the value of the external specific surface area by the T-plot method derived from the results of nitrogen adsorption measurement according to JIS Z8831-2:2010 from the value of the BET specific surface area derived from the results of nitrogen adsorption measurement according to JIS Z8830:2013, i.e., the value of the total specific surface area. Regarding condition ii), the value of the average primary particle diameter is derived from an SEM photograph of the carbon raw material. Regarding condition iii), the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of the carbon raw material is selected as a measure of the crystallinity of the carbon raw material. Non-Patent Document 1 (Ore Geology Reviews 70 (2015) 80-95) states that in the Raman spectrum of a highly crystalline graphite structure, the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band is selected as a measure of the crystallinity of the carbon raw material. -1 The S1 band is observed near 2900 cm when the graphite structure is disturbed. -1 The S1 band appears near the S2 band (see A and B in Figure 3 of this document). When the crystal structure is disturbed, the peak intensity of the S2 band increases relatively, so the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum can be effectively used as a measure of the crystallinity of the carbon raw material.
[0020] For carbon that does not satisfy any one of the above conditions i), ii), or iii), it is difficult to impart the property of turning into a paste when subjected to pressure with an oxidation treatment of the same intensity as that applied to Ketjen black. Furthermore, even if an electrode is manufactured by a dry process using carbon after the oxidation treatment, it is not possible to suppress the generation of voids in the electrode, and an electrode with high electrode density cannot be obtained.
[0021] Regarding condition i), the internal specific surface area of the carbon as the carbon raw material is 30 m 2 / g or less, but preferably 1 to 25 m 2 / g range. 2 Ketjenblack has a total specific surface area of approximately 650 m 2As can be seen from this, the internal specific surface area is 30 m 2 / g or less, preferably 1 to 25m 2 / g means that the carbon particles have almost no pores. Regarding condition ii), the average primary particle size of the carbon as the carbon raw material may be 35 nm or less, but is preferably in the range of 10 to 34 nm, and regarding condition iii), the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of the carbon as the carbon raw material may be 1.00 or less, but is preferably in the range of 0.93 to 0.99.
[0022] In the method for producing the oxidized carbon of the present invention, it is preferable to carry out the oxidation treatment in the oxidation step so that the content of the hydrophilic portion in the obtained oxidized carbon is 10% by mass or more of the entire oxidized carbon, since the property of the oxidized carbon spreading like a paste when pressure is applied becomes prominent. The "hydrophilic portion" of the oxidized carbon has the following meaning. That is, 0.1 g of the oxidized carbon is added to 20 mL of an aqueous ammonia solution of pH 11, ultrasonic irradiation is performed for 1 minute, and the resulting liquid is left for 5 hours to precipitate the solid phase portion. The portion that does not precipitate and is dispersed in the aqueous ammonia solution of pH 11 is the "hydrophilic portion". The content of the hydrophilic portion in the entire oxidized carbon is determined by the following method. After the precipitation of the solid phase portion, the remaining portion after removing the supernatant liquid is dried, and the weight of the solid after drying is measured. The weight obtained by subtracting the weight of the solid after drying from the weight of the initial oxidized carbon of 0.1 g is the weight of the "hydrophilic portion" dispersed in the aqueous ammonia solution of pH 11. The weight ratio of the "hydrophilic portion" to the initial weight of the oxidized carbon (0.1 g) is the content of the "hydrophilic portion" in the oxidized carbon.
[0023] The present invention also relates to a method for producing a carbon mixture to be used as a conductive agent in an electrode of an electrical storage device, comprising the steps of: A mixing step in which the oxidized carbon obtained by the method for producing oxidized carbon of the present invention is dry-mixed with another conductive carbon having a higher conductivity than that of the oxidized carbon to obtain a carbon mixture in which at least a part of the oxidized carbon spreads in a paste-like form and adheres to the surface of the other conductive carbon. The carbon mixture is preferably used when high electrical conductivity is required for the electrode.
[0024] The method for producing a carbon mixture of the present invention requires the above-mentioned mixing step, but by performing a heat treatment step in a vacuum or a non-oxidizing atmosphere following the mixing step, the amount of CO2 generated from the carbon mixture after the heat treatment in the range of 25 to 200 ° C. is reduced from the amount of CO2 generated from the carbon mixture before the heat treatment in the range of 25 to 200 ° C. The heat treatment step improves the charge / discharge cycle stability of an electric storage device equipped with an electrode using the obtained carbon mixture when a high voltage is applied, and therefore the operating voltage of the obtained electric storage device can be expanded. In addition, since the heat treatment does not affect the property of the oxidized carbon to turn into a paste when subjected to pressure, the high electrode density of the electrode of the electric storage device produced through the dry process is maintained. Note that the "amount of CO2 generated from the carbon mixture in the range of 25 to 200 ° C." has the following meaning. An experiment is conducted to measure the amount of CO2 generated while heating 30 mg of the carbon mixture to be measured using a temperature programmed desorption photoionization mass spectrometry (TPD-PIMS) device under conditions of atmospheric pressure helium atmosphere (helium flow rate 300 mL / min), temperature range from room temperature to 1200°C, and heating rate of 20°C / min. The total amount (integral value) of CO2 generated in the temperature range of 25 to 200°C calculated from the obtained experimental results is the "amount of CO2 generated from the carbon mixture in the range of 25 to 200°C."
[0025] The oxidized carbon and carbon mixture obtained by the manufacturing method of the present invention are suitable for manufacturing electrodes for electricity storage devices by a dry process, and provide electrodes with high electrode density, and ultimately provide electricity storage devices with high energy density.
[0026] Therefore, the present invention also provides a method for producing an electrode for an electricity storage device, comprising the steps of: a dry mixing step of dry-mixing electrode active material particles with the oxidation-treated carbon obtained by the production method of the present invention to obtain an electrode mixture in which at least a part of the oxidation-treated carbon spreads in a paste-like form and adheres to the surfaces of the electrode active material particles; and A dry pressing process is performed on the electrode mixture to obtain an electrode in which the oxidized carbon is further spread in a paste-like form and densified. The present invention relates to a method for producing an electrode, comprising the steps of:
[0027] The present invention further provides a method for producing an electrode for an electricity storage device, comprising the steps of: a dry mixing step of dry-mixing electrode active material particles with a carbon mixture obtained by the production method of the present invention to obtain an electrode mixture in which at least a part of the carbon originating from the oxidation-treated carbon spreads in a paste-like form and adheres not only to the surface of the separate conductive carbon but also to the surface of the electrode active material particles; and A dry pressing process is performed on the electrode mixture to obtain an electrode in which at least a part of the carbon derived from the oxidized carbon, which has spread in a paste-like form, further spreads in a paste-like form and becomes densified. In the present specification, the portion of the carbon mixture derived from the oxidation-treated carbon is referred to as "carbon derived from the oxidation-treated carbon."
[0028] The method for producing an electrode using the carbon mixture obtained by the production method of the present invention is suitable for producing an electrode for an all-solid-state battery having an electrolyte layer composed of an inorganic solid electrolyte, an organic solid electrolyte, or a gel electrolyte. The obtained electrode has a high electrode density, so that the migration distance of ions responsible for the transfer of electrons with the electrode active material particles can be shortened. For producing an electrode for an all-solid-state battery, in the dry mixing step, in addition to the electrode active material particles and the carbon mixture, solid electrolyte particles for forming an ion conduction path between the electrolyte layer and the electrode active material particles are dry mixed to obtain an electrode mixture, which is then followed by the dry pressing step.
[0029] In the dry mixing step, the electrode mixture may be obtained by dry-mixing the entire amount of the solid electrolyte particles used for the electrode mixture together with the electrode active material particles and the carbon mixture obtained by the production method of the present invention. However, the electrode mixture may be obtained by performing the dry mixing step without dry-mixing the entire amount of the solid electrolyte particles together. A first step of dry-mixing the carbon mixture with a portion of the solid electrolyte particles used for the electrode mixture; A second step of dry-mixing the mixture obtained in the first step with the electrode active material particles; and A third step of dry-mixing the mixture obtained in the second step with the remaining solid electrolyte particles to obtain a mixture for an electrode. It is preferable to carry out the dry mixing process including the first to third steps, followed by the dry pressing process. When the dry mixing process including the first to third steps is carried out, the electrode density is increased compared to when the entire amount of the solid electrolyte particles is dry mixed together with the electrode active material particles and the carbon mixture. This method is particularly suitable when sulfide-based solid electrolyte particles are used as the solid electrolyte particles. Effect of the Invention
[0030] The oxidized carbon having the property of turning into a paste-like substance when subjected to pressure and the carbon mixture containing the oxidized carbon obtained by the manufacturing method of the present invention, which are to be used as conductive agents in electrodes of electricity storage devices, can suppress the occurrence of voids inside the electrodes of electricity storage devices manufactured via a dry process, thereby increasing the electrode density. [Brief description of the drawings]
[0031] [Figure 1] This is an SEM photograph confirming the paste-like nature of the oxidized carbon. [Diagram 2] 1 is a SEM photograph of a cross section of an electrode produced via a dry process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] (1) Manufacturing method of oxidized carbon The method for producing oxidized carbon to be used as a conductive agent in an electrode of an electricity storage device in the present invention includes an oxidation step of obtaining oxidized carbon having a property of turning into a paste-like substance when pressure is applied by subjecting a conductive carbon raw material to an oxidation treatment, and the carbon raw material is oxidized under the following conditions i), ii), and iii): i) Internal specific surface area is 30m 2 / g or less, preferably 1 to 25m 2 / g range, ii) the average primary particle size is 35 nm or less, preferably in the range of 10 to 34 nm; iii) the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum is 1.00 or less, preferably in the range of 0.93 to 0.99; For carbon that does not satisfy any one of the above conditions i), ii), and iii), it is difficult to impart the property of turning into a paste when subjected to pressure with an oxidation treatment of the same intensity as that applied to Ketjen Black, and even if an electrode is obtained by a dry process using the carbon after the oxidation treatment, it is not possible to suppress the generation of voids in the electrode, and it is not possible to obtain an electrode having a high electrode density.
[0033] The carbon used as the carbon raw material and satisfying the above conditions i), ii), and iii) can be selected from, for example, commercially available carbon black. Two or more types of carbon may be mixed and used as long as they satisfy all of the above conditions i), ii), and iii).
[0034] In order to oxidize carbon that satisfies all of the above conditions i), ii), and iii) as a carbon raw material, a known oxidation method can be used without any particular limitation. For example, the oxidized carbon can be obtained by treating the carbon in an acid or hydrogen peroxide solution. As the acid, nitric acid, a nitric acid-sulfuric acid mixture, an aqueous hypochlorous acid solution, etc. can be used. The oxidized carbon can be obtained by heating the carbon in an oxygen-containing atmosphere, water vapor, or carbon dioxide. The oxidized carbon can be obtained by mixing the carbon with an alkali metal hydroxide, heating it in an oxygen-containing atmosphere, and removing the alkali metal by washing with water, etc. The oxidized carbon can be obtained by subjecting the carbon to a plasma treatment, ultraviolet light irradiation, corona discharge treatment, glow discharge treatment, treatment with ozone water or ozone gas, or oxygen bubbling treatment in water in an oxygen-containing atmosphere.
[0035] When carbon that satisfies all of the above conditions i), ii) and iii) is subjected to oxidation treatment, the surface of the carbon particles is oxidized, hydroxyl groups, carboxyl groups and ether bonds are introduced into the carbon, the conjugated double bonds of the carbon are oxidized to form carbon single bonds, the carbon-carbon bonds are partially broken, and hydrophilic parts are formed on the particle surface. Then, by increasing the intensity of the oxidation treatment, the carbon can be given the property of spreading like a paste when pressure is applied. The content of the hydrophilic part in the oxidation treated carbon is preferably 10% by mass or more of the entire oxidation treated carbon. Such oxidation treated carbon is easily compressed as a whole and spreads like a paste when pressure is applied, and is easily densified.
[0036] To produce an oxidized carbon containing 10% by mass or more of a hydrophilic portion, (a1) treating carbon that satisfies all of the above conditions i), ii) and iii) with an acid; (b1) mixing the product after the acid treatment with a transition metal compound; (c1) grinding the mixture to cause a mechanochemical reaction; (d1) heating the product after the mechanochemical reaction in a non-oxidizing atmosphere; and (e1) removing the transition metal compound and / or its reaction product from the product after heating; The first production method including the steps of:
[0037] In step (a1), the carbon is immersed in acid and left to stand. Ultrasonic irradiation may be used during this immersion. The acid may be an acid normally used in the oxidation treatment of carbon, such as nitric acid, a mixture of nitric acid and sulfuric acid, or an aqueous solution of hypochlorous acid. The immersion time depends on the concentration of the acid and the amount of carbon to be treated, but is generally in the range of 5 minutes to 5 hours. After the acid treatment, the carbon is thoroughly washed with water and dried, and then mixed with a transition metal compound in step (b1).
[0038] In step (b1), the transition metal compound added to the carbon after the acid treatment can be an inorganic metal salt such as a halide, nitrate, sulfate, or carbonate of a transition metal, or an organic metal salt such as a formate, acetate, oxalate, methoxide, ethoxide, or isopropoxide, or a mixture thereof. These compounds can be used alone or in combination of two or more. Compounds containing different transition metals can be mixed and used in a predetermined amount. In addition, as long as they do not adversely affect the reaction, a compound other than the transition metal compound, for example, an alkali metal compound, can be added together. Since the oxidation-treated carbon produced by the production method of the present invention is mixed with electrode active material particles and used in the production of electrodes for a power storage device, it is preferable to add a compound of an element constituting the electrode active material to the carbon after the acid treatment, since it is possible to prevent the inclusion of elements that may become impurities in the active material.
[0039] In step (c1), the mixture obtained in step (b1) is pulverized to cause a mechanochemical reaction. Examples of pulverizers for this reaction include a Raikai mill, a ball mill, a bead mill, a rod mill, a roller mill, an agitator mill, a planetary mill, a vibration mill, a hybridizer, a mechanochemical composite device, and a jet mill. The pulverization time depends on the pulverizer used and the amount of carbon to be treated, and is not strictly limited, but is generally in the range of 5 minutes to 3 hours. Step (d1) is performed in a non-oxidizing atmosphere such as a nitrogen atmosphere or an argon atmosphere. The heating temperature and heating time are appropriately selected depending on the transition metal compound used. In the subsequent step (e1), the transition metal compound and / or its reaction product are removed from the product after heating by means of dissolving it in an acid, etc., and then the product is thoroughly washed and dried to obtain an oxidized carbon.
[0040] In the first manufacturing method, in step (c1), the transition metal compound acts to promote the oxidation of the carbon through a mechanochemical reaction, and the oxidation of the carbon proceeds rapidly, resulting in the carbon being endowed with the property of spreading like a paste when subjected to pressure.
[0041] For the production of oxidized carbon containing 10% by mass or more of hydrophilic moieties, (a2) mixing carbon that satisfies all of the above conditions i), ii) and iii) with a transition metal compound; (b2) heating the resulting mixture in an oxidizing atmosphere; and (c2) removing the transition metal compound and / or its reaction product from the product after heating. The second production method including the steps of:
[0042] In step (a2), the transition metal compound added to the carbon may be an inorganic metal salt such as a transition metal halide, nitrate, sulfate, or carbonate, an organic metal salt such as a formate, acetate, oxalate, methoxide, ethoxide, or isopropoxide, or a mixture thereof. These compounds may be used alone or in combination of two or more. Compounds containing different metals may be mixed and used in a predetermined amount. In addition, as long as they do not adversely affect the reaction, a compound other than the transition metal compound, for example, an alkali metal compound, may be added together. Since the oxidized carbon produced by the production method of the present invention is mixed with electrode active material particles in the production of electrodes for a power storage device, it is preferable to add a compound of an element constituting the electrode active material to the carbon, since this can prevent the inclusion of elements that may become impurities in the active material.
[0043] Step (b2) is carried out in an oxygen-containing atmosphere, for example, air, at a temperature at which the carbon is partially but not completely lost, preferably at a temperature of 200 to 350° C. In the subsequent step (c2), the transition metal compound and / or its reaction product is removed from the product after heating by means of dissolving it in an acid or the like, and then the product is thoroughly washed and dried to obtain oxidized carbon.
[0044] In the second manufacturing method, in step (b2), the transition metal compound acts as a catalyst for oxidizing the carbon, and the oxidation of the carbon proceeds rapidly, resulting in the carbon being endowed with the property of spreading like a paste when subjected to pressure.
[0045] In the oxidation step of the production method of the present invention, it is also possible to promote the oxidation of the carbon raw material by a method other than the first production method and the second production method.
[0046] The oxidation-treated carbon obtained by the above-mentioned manufacturing method is used as it is, or after being subjected to a pulverization treatment to homogenize the particle size, etc. as necessary, in the manufacturing method of the carbon mixture described below, and is also used as a conductive agent in the manufacture of electrodes for electricity storage devices by a dry process. There are no particular limitations on the method of pulverization treatment as necessary, and it may be performed by hand mixing using a mortar, or it may be performed using a known mixing device such as a mortar, a ball mill, a bead mill, a rod mill, a roller mill, a stirring mill, a planetary mill, a vibration mill, a hybridizer, a mechanochemical composite device, a jet mill, or a rotation-revolution mixer.
[0047] (2) Manufacturing method of carbon mixture A method for producing a carbon mixture to be used as a conductive agent in an electrode of an electricity storage device according to the present invention includes the steps of: A mixing step in which the oxidized carbon obtained by the above-mentioned manufacturing method is dry-mixed with another conductive carbon having a higher conductivity than that of the oxidized carbon to obtain a carbon mixture in which at least a part of the oxidized carbon spreads in a paste-like form and adheres to the surface of the other conductive carbon. Includes.
[0048] In the mixing step, examples of the other conductive carbon to be dry-mixed with the oxidation-treated carbon include carbon blacks such as ketjen black, acetylene black, furnace black, and channel black, which are used for electrodes of conventional electricity storage devices, fullerenes, carbon nanotubes, carbon nanofibers, graphene, amorphous carbon, carbon fibers, natural graphite, artificial graphite, graphitized ketjen black, mesoporous carbon, and vapor-grown carbon fibers. If the conductivity of the other conductive carbon is 15 S / cm or more, an electrode having high conductivity can be obtained, which is preferable. The mass ratio of the oxidation-treated carbon to the other conductive carbon is generally in the range of 9:1 to 1:9.
[0049] There is no particular limitation on the method of dry mixing the oxidation-treated carbon and the other conductive carbon, and the mixture may be mixed by hand using a mortar, or may be mixed using a known mixing device such as a mortar, a ball mill, a bead mill, a rod mill, a roller mill, an agitator mill, a planetary mill, a vibration mill, a hybridizer, a mechanochemical composite device, a jet mill, or a rotation / revolution mixer. Since the oxidation-treated carbon has the property of spreading in a paste-like manner when subjected to pressure, at least a part of the oxidation-treated carbon spreads in a paste-like manner and adheres to the surface of the other conductive carbon during the mixing stage due to the pressure applied to the oxidation-treated carbon. The dry mixing time depends on the pulverizer used, the amount of carbon to be treated, etc., and is not strictly limited as long as a carbon mixture in which at least a part of the oxidation-treated carbon spreads in a paste-like manner and adheres to the surface of the other conductive carbon is obtained, but is generally in the range of 10 minutes to 1 hour.
[0050] In the case where charge / discharge cycle stability at high voltage application is required for the electricity storage device, following the above mixing step, A heat treatment step in which the carbon mixture obtained in the mixing step is heat-treated in a vacuum or a non-oxidizing atmosphere to reduce the amount of CO2 generated from the carbon mixture after the heat treatment in the range of 25 to 200°C compared to the amount of CO2 generated from the carbon mixture before the heat treatment in the range of 25 to 200°C. The charge-discharge cycle stability during application of high voltage in an electricity storage device tends to decrease when the number of substituents on the surface of the oxidation-treated carbon constituting the carbon mixture is large. However, it has been found that when the carbon mixture is heat-treated in a vacuum or in a non-oxidizing atmosphere, the amount of CO2 generated in the range of 25 to 200°C, which is mainly caused by detachment from the carboxyl group on the surface of the oxidation-treated carbon, can be greatly reduced, and accordingly, improved charge-discharge cycle stability can be obtained in a charge-discharge cycle test during application of high voltage (see Patent Document 3). Moreover, the property of the oxidation-treated carbon contained in the carbon mixture before the heat treatment, which spreads like a paste when subjected to pressure, is maintained in the oxidation-treated carbon contained in the carbon mixture after the heat treatment, so this heat treatment does not affect the density of the electrodes of the electricity storage device.
[0051] The non-oxidizing atmosphere for the heat treatment may be composed of an inert gas such as nitrogen or argon, a reducing gas such as hydrogen or carbon monoxide, or a mixed gas of an inert gas and a reducing gas. The temperature and time of the heat treatment vary depending on the amount of the carbon mixture to be treated and the type of the heat treatment atmosphere. For example, when the heat treatment atmosphere is a nitrogen atmosphere, the treatment conditions can be 2 to 8 hours at a temperature of 200°C or more and less than 500°C, or 0.5 to 2 hours at a temperature of 500°C or more and 900°C or less.
[0052] The carbon mixture obtained by the above-mentioned manufacturing method is used as a conductive agent in the manufacture of an electrode for an electricity storage device by the dry process described below.
[0053] The above-mentioned heat treatment in a vacuum or in a non-oxidizing atmosphere can be applied not only to the carbon mixture but also to the oxidized carbon.
[0054] (3) Electrode manufacturing method The oxidized carbon and carbon mixture obtained by the manufacturing method of the present invention are used in the form of a mixture with particles of an electrode active material that exhibits capacity by a Faraday reaction involving the transfer of electrons with ions in the electrolyte of the electricity storage device or a non-Faraday reaction not involving the transfer of electrons, for use in electrodes of electricity storage devices such as secondary batteries, electric double layer capacitors, redox capacitors, and hybrid capacitors. An electricity storage device essentially comprises a pair of electrodes (positive electrode, negative electrode) and an electrolyte disposed between them, and at least one of the positive electrode and negative electrode is manufactured using a mixture containing electrode active material particles and the oxidized carbon or carbon mixture obtained by the manufacturing method of the present invention as a conductive agent.
[0055] The electrolyte disposed between the positive electrode and the negative electrode may be an electrolyte solution held in a separator, may be a solid electrolyte, or may be a gel electrolyte, and any electrolyte used in conventional power storage devices may be used without any particular limitation. Representative electrolytes are exemplified below. For lithium ion secondary batteries, electrolytes obtained by dissolving lithium salts such as LiPF6, LiBF4, LiCF3SO3, and LiN(CF3SO2)2 in a solvent such as ethylene carbonate, propylene carbonate, butylene carbonate, and dimethyl carbonate are used in a state held by a separator such as a polyolefin fiber nonwoven fabric or a glass fiber nonwoven fabric. In addition, inorganic solid electrolytes such as sulfide-based inorganic solid electrolytes such as Li6PS5X (X=Cl, Br, I), Li2S-P2S5, and Li2S-P2S5-LiI, Li7La3Zr2O5, La 0.57 Li 0.29 TiO3, Li 1+x Al x Ge y Ti 2-x-y P3O 12Inorganic solid electrolytes based on oxides such as -AlPO4, organic solid electrolytes consisting of a complex of lithium salt and polymer compounds such as polyethylene oxide, polymethacrylate, and polyacrylate, and gel electrolytes in which electrolyte is absorbed in polyvinylidene fluoride, polyacrylonitrile, etc. are also used. For electric double layer capacitors and redox capacitors, electrolytes in which quaternary ammonium salts such as (C2H5)4NBF4 are dissolved in solvents such as acrylonitrile and propylene carbonate are used. For hybrid capacitors, electrolytes in which lithium salts are dissolved in propylene carbonate, etc. and electrolytes in which quaternary ammonium salts are dissolved in propylene carbonate, etc. are used.
[0056] As the electrode active materials for the positive and negative electrodes, any electrode active materials used in conventional power storage devices can be used without any particular limitation. The electrode active material may be a single compound or a mixture of two or more compounds.
[0057] Examples of positive electrode active materials for secondary batteries include layered rock salt LiMO2, layered Li2MnO3-LiMO2 solid solution, and spinel LiM2O4 (wherein M is Mn, Fe, Co, Ni, or a combination thereof). Specific examples of these include LiCoO2, LiNiO2, LiNi 4 / 5 Co 1 / 5 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 1 / 2 Mn 1 / 2 O2, LiFeO2, LiMnO2, Li2MnO3-LiCoO2, Li2MnO3-LiNiO2, Li2MnO3-LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li2MnO3-LiNi 1 / 2 Mn 1 / 2 O2, Li2MnO3-LiNi 1 / 2 Mn 1 / 2 O2-LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMn2O4, LiMn 3 / 2Ni 1 / 2 O4. Sulfur and Li2S, TiS2, MoS2, FeS2, VS2, Cr 1 / 2 V 1 / 2 Sulfides such as S2, selenides such as NbSe3, VSe2, NbSe3, Cr2O5, Cr3O8, VO2, V3O8, V2O5, V6O 13 In addition to oxides such as LiNi 0.8 Co 0.15 Al 0.05 O2, LiVOPO4, LiV3O5, LiV3O8, MoV2O8, Li2FeSiO4, Li2MnSiO4, LiFePO4, LiFe 1 / 2 Mn 1 / 2 Examples include complex oxides such as PO4, LiMnPO4, and Li3V2(PO4)3.
[0058] Examples of negative electrode active materials for secondary batteries include oxides such as Fe2O3, MnO, MnO2, Mn2O3, Mn3O4, CoO, Co3O4, NiO, Ni2O3, TiO, TiO2, SnO, SnO2, SiO2, RuO2, WO, WO2, and ZnO, metals such as Sn, Si, Al, and Zn, LiVO2, Li3VO4, and Li4Ti5O 12 Complex oxides such as Li 2.6 Co 0.4 Nitrides such as N, Ge3N4, Zn3N2, and Cu3N.
[0059] Examples of the active material in the polarizable electrode of the electric double layer capacitor include carbon materials with a large specific surface area, such as activated carbon, carbon nanofibers, carbon nanotubes, phenolic resin carbide, polyvinylidene chloride carbide, and microcrystalline carbon. In the hybrid capacitor, the positive electrode active material exemplified for the secondary battery can be used for the positive electrode, and in this case, the negative electrode is composed of a polarizable electrode using activated carbon or the like. Also, the negative electrode active material exemplified for the secondary battery can be used for the negative electrode, and in this case, the positive electrode is composed of a polarizable electrode using activated carbon or the like. Examples of the positive electrode active material of the redox capacitor include metal oxides such as RuO2, MnO2, and NiO, and the negative electrode is composed of an active material such as RuO2 and a polarizable material such as activated carbon.
[0060] Although there is no limitation on the shape or particle size of the electrode active material particles, it is preferable that the average particle size is greater than 2 μm and not greater than 25 μm. The electrode active material particles having such a relatively large particle size not only improve the electrode density by themselves, but also promote the gelatinization of the oxidized carbon by the pressing force of the electrode active material particles in the dry mixing step and the dry pressing step described below.
[0061] When an electrode for an electricity storage device is manufactured using the oxidized carbon obtained by the manufacturing method of the present invention, a dry mixing step of dry-mixing electrode active material particles with the oxidized carbon to obtain an electrode mixture in which at least a portion of the oxidized carbon spreads in a paste-like form and adheres to the surfaces of the electrode active material particles; and A dry pressing process is performed on the electrode mixture to obtain an electrode in which the oxidized carbon is further spread in a paste-like form and densified. A method is carried out comprising:
[0062] When an electrode for an electricity storage device is manufactured using the carbon mixture obtained by the manufacturing method of the present invention, a dry mixing step of dry-mixing electrode active material particles with the carbon mixture to obtain an electrode mixture in which at least a part of the carbon originating from the oxidized carbon spreads in a paste-like form and adheres not only to the surface of the separate conductive carbon but also to the surface of the electrode active material particles; and A dry pressing process is performed on the electrode mixture to obtain an electrode in which at least a part of the carbon derived from the oxidized carbon, which has spread in a paste-like form, further spreads in a paste-like form and becomes densified. A method is carried out comprising:
[0063] The method of dry mixing in the dry mixing step is not particularly limited, and may be performed by hand mixing using a mortar, or may be performed using a known mixing device such as a mortar, a ball mill, a bead mill, a rod mill, a roller mill, an agitation mill, a planetary mill, a vibration mill, a hybridizer, a mechanochemical composite device, a jet mill, or a rotation / revolution mixer. The dry mixing time varies depending on the device used for dry mixing and the amount of material to be processed. There is no strict limit to the dry mixing time as long as an electrode mixture in which at least a part of the oxidation-treated carbon spreads in a paste-like form and adheres to the surface of the electrode active material particles is obtained, or an electrode mixture in which at least a part of the oxidation-treated carbon in the carbon mixture spreads in a paste-like form and adheres not only to the surface of the other conductive carbon but also to the surface of the electrode active material particles is obtained, but it is generally in the range of 5 minutes to 3 hours.
[0064] The electrode active material particles and the oxidized carbon or the carbon mixture are preferably dry mixed in a mass ratio of 90:10 to 99.5:0.5, more preferably 95:5 to 99:1. If the amount of the oxidized carbon or the carbon mixture is less than the above range, the conductivity of the resulting electrode is insufficient, and the adhesion rate of the oxidized carbon or the carbon mixture to the surface of the electrode active material particles tends to decrease. If the amount of the oxidized carbon or the carbon mixture is more than the above range, the electrode density tends to decrease, and the energy density of the electricity storage device tends to decrease.
[0065] The method for manufacturing an electrode using the carbon mixture is suitable for manufacturing an electrode for an all-solid-state battery having an electrolyte layer composed of an inorganic solid electrolyte, an organic solid electrolyte, or a gel electrolyte. The obtained electrode has a high electrode density, so that the moving distance of ions that transfer electrons to and from the electrode active material particles can be shortened. For manufacturing an electrode for an all-solid-state battery, in addition to the electrode active material particles and the carbon mixture, solid electrolyte particles for forming an ion conduction path between the electrolyte layer and the electrode active material particles are dry-mixed to obtain an electrode mixture, followed by the dry pressing step. The solid electrolyte particles to be dry-mixed are selected so as to be compatible with the electrolyte layer of the all-solid-state battery, and are selected from sulfide-based solid electrolyte particles such as Li6PS5X (X=Cl, Br, I), Li2S-P2S5, Li2S-P2S5-LiI, Li7La3Zr2O5, La 0.57 Li 0.29 TiO3, Li 1+x Al x Ge y Ti 2-x-y P3O 12 Examples include particles of oxide-based solid electrolyte such as AlPO4.
[0066] When obtaining an electrode mixture containing solid electrolyte particles in the dry mixing step, there is no particular limitation on the order of mixing the electrode active material particles, the solid electrolyte particles, and the carbon mixture, and all of them may be mixed at the same time. However, it is also possible to dry-mix the entire amount of the solid electrolyte particles together, and to carry out the dry mixing step in the following order: A first step of dry-mixing a portion of the solid electrolyte particles used for the electrode mixture with the carbon mixture; A second step of dry-mixing the mixture obtained in the first step with the electrode active material particles; and A third step of dry-mixing the mixture obtained in the second step with the remaining solid electrolyte particles to obtain a mixture for an electrode. is preferably carried out by the method including the steps of: (a) mixing the entire amount of the solid electrolyte particles together with the electrode active material particles and the carbon mixture in a dry state;
[0067] The method of dry mixing when obtaining an electrode mixture containing solid electrolyte particles is not particularly limited, including the case where dry mixing is performed by the above-mentioned first to third steps, and may be performed by hand mixing using a mortar, or may be performed using a known mixing device such as a mortar, a ball mill, a bead mill, a rod mill, a roller mill, an agitator mill, a planetary mill, a vibration mill, a hybridizer, a mechanochemical composite device, a jet mill, a rotation / revolution mixer, etc. There is no strict limit to the dry mixing time as long as an electrode mixture is obtained in which at least a part of the carbon derived from the oxidized carbon in the carbon mixture is spread in a paste-like form and adheres not only to the surface of the other conductive carbon but also to the surface of the electrode active material particles and the surface of the solid electrolyte particles.
[0068] The property of the oxidation-treated carbon obtained by the manufacturing method of the present invention to change into a paste-like form when subjected to pressure is useful for integrally forming an electrode, so that the binder used in the manufacture of normal electrodes is not essential in the manufacturing method of the electrode of the present invention. However, when an electrode having high strength is particularly required, a small amount of a binder can be dry-mixed in the dry mixing step in addition to the electrode active material particles, the oxidation-treated carbon or the carbon mixture, and the solid electrolyte particles, if present, to obtain an electrode mixture. As the binder, known binders such as polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, and carboxymethyl cellulose are used.
[0069] The dry pressing step following the dry mixing step can be carried out by forming an active material layer by laminating the obtained electrode mixture on a current collector by a known method such as electrostatic screen printing, and applying pressure to the active material layer. The electrode mixture may be introduced into a predetermined frame, and then molded by applying pressure, and the molded product obtained may be pressed onto a current collector to carry out the dry pressing step. When pressure is applied to the electrode mixture in the dry pressing step, the oxidized carbon, at least a part of which has been changed to a paste-like state, spreads further and densifies while covering the surfaces of the electrode active material particles and, if present, the surfaces of the solid electrolyte particles, and the electrode active material particles approach each other accordingly. Therefore, the amount of active material per unit volume in the electrode increases, and the electrode density increases. As the current collector, conductive materials such as platinum, gold, nickel, aluminum, titanium, steel, and carbon can be used. The shape of the current collector can be a film, a foil, a plate, a net, or the like. The pressure range in the dry pressing is generally 10 to 1500 MPa, preferably 50 to 1000 MPa. There is no particular limitation on the temperature of the dry pressing treatment, and the treatment may be carried out at room temperature or under heated conditions. EXAMPLES
[0070] The present invention will be described with reference to the following examples, but the present invention is not limited to the following examples.
[0071] (1) Manufacturing of oxidized carbon Example 1 As a carbon raw material, the total specific surface area is 265m 2 / g, and the external specific surface area is 256m 2 / g, and the internal specific surface area obtained from these values is 9m 2Carbon black with a molecular weight of 1.01g / g, an average primary particle size of 14nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 0.958 was used. 10g of this carbon raw material was added to 300mL of 60% nitric acid, and the resulting liquid was irradiated with ultrasonic waves for 10 minutes, and then filtered to recover the carbon. The recovered carbon was washed with water three times and dried to obtain acid-treated carbon. 0.5g of this acid-treated carbon, 1.98g of Fe(CH3COO)2, 0.77g of Li(CH3COO), 1.10g of C6H8O7·H2O, 1.32g of CH3COOH, 1.31g of H3PO4, and 120mL of distilled water were mixed, and the resulting mixture was stirred with a stirrer for 1 hour, and then evaporated to dryness at 100°C in air to collect the mixture. The resulting mixture was then introduced into a vibration ball mill and pulverized at 20Hz for 10 minutes. The ground powder was heated in nitrogen at 700°C for 3 minutes to obtain a composite in which LiFePO4 was supported on carbon.
[0072] 1 g of the resulting complex was added to 100 mL of a 30% aqueous hydrochloric acid solution, and the resulting solution was irradiated with ultrasonic waves for 15 minutes to dissolve the LiFePO4 in the complex, and the remaining solid was filtered, washed with water, and dried. A part of the dried solid was heated to 900°C in air by TG analysis to measure the weight loss. The above-mentioned process of dissolving LiFePO4 in an aqueous hydrochloric acid solution, filtering, washing with water, and drying was repeated until it was confirmed that the weight loss was 100%, that is, no LiFePO4 remained, to obtain LiFePO4-free oxidation-treated carbon. The content of hydrophilic portions in this oxidation-treated carbon was 11 mass% of the total.
[0073] In order to confirm whether the above-mentioned oxidation-treated carbon has the property of turning into a paste when subjected to pressure, 2 parts by mass of the above-mentioned oxidation-treated carbon and LiNi 0.5 Mn 0.3 Co 0.296 parts by mass of O2 particles (average particle size 5 μm) were introduced and dry mixed at 2000 rpm for 5 minutes, and then 2 parts by mass of N-methylpyrrolidone containing polyvinylidene fluoride was further introduced and kneaded. The kneaded mixture obtained was applied to an aluminum foil and dried, and an SEM photograph of the dried product was taken to confirm whether the oxidized carbon had changed to a paste-like state.
[0074] Example 2 Instead of the carbon raw material used in Example 1, a carbon fiber having a total specific surface area of 118 m 2 / g, and the external specific surface area is 111m 2 / g, and the internal specific surface area obtained from these values is 7m 2 The procedure shown in Example 1 was repeated, except that carbon black having a molecular weight of 1.0 / g, an average primary particle size of 22 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 0.977 was used as the carbon raw material.
[0075] Example 3 Instead of the carbon raw material used in Example 1, a carbon fiber having a total specific surface area of 220 m 2 / g, and the external specific surface area is 200m 2 / g, and the internal specific surface area obtained from these values is 20m 2 The procedure shown in Example 1 was repeated, except that carbon black having a molecular weight of 1.0 / g, an average primary particle size of 23 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 0.955 was used as the carbon raw material.
[0076] Example 4 Instead of the carbon raw material used in Example 1, a carbon fiber having a total specific surface area of 225 m 2 / g, and the external specific surface area is 215m 2 / g, and the internal specific surface area obtained from these values is 10m 2The procedure shown in Example 1 was repeated, except that carbon black having a molecular weight of 1.0 / g, an average primary particle size of 25 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 0.943 was used as the carbon raw material.
[0077] Example 5 Instead of the carbon raw material used in Example 1, a carbon fiber having a total specific surface area of 59 m 2 / g, and the external specific surface area is 43m 2 / g, and the internal specific surface area obtained from these values is 16m 2 The procedure shown in Example 1 was repeated, except that carbon black having a molecular weight of 1.001 g / g, an average primary particle size of 31 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 0.967 was used as the carbon raw material.
[0078] Comparative Example 1 Instead of the carbon raw material used in Example 1, a carbon fiber having a total specific surface area of 52 m 2 / g, and the external specific surface area is 51m 2 / g, and the internal specific surface area obtained from these values is 1 m 2 The procedure shown in Example 1 was repeated, except that carbon black having a molecular weight of 1.0 / g, an average primary particle size of 40 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 0.981 was used as the carbon raw material.
[0079] Comparative Example 2 Instead of the carbon raw material used in Example 1, a carbon fiber having a total specific surface area of 77 m 2 / g, and the external specific surface area is 70m 2 / g, and the internal specific surface area obtained from these values is 7m 2 The procedure shown in Example 1 was repeated, except that carbon black having a molecular weight of 1.01 / g, an average primary particle size of 22 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 13.01 was used as the carbon raw material.
[0080] Comparative Example 3 Instead of the carbon raw material used in Example 1, a carbon fiber having a total specific surface area of 57 m 2 / g, and the external specific surface area is 54m 2 / g, and the internal specific surface area obtained from these values is 3m 2 The procedure shown in Example 1 was repeated, except that carbon black having a molecular weight of 1.0 / g, an average primary particle size of 40 nm, and a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 12.01 was used as the carbon raw material.
[0081] Reference example 1 Instead of the carbon raw material used in Example 1, Ketjen Black EC300J (total specific surface area value of 788 m 2 / g, and the external specific surface area is 139m 2 / g, and the internal specific surface area obtained from these values is 647 m 2 The procedure given in Example 1 was repeated, except that 1,2-dichloroethane (C10 / g) was used as the carbon source.
[0082] Fig. 1 shows an SEM photograph of a mixture containing the oxidation treated carbon of Example 1 and electrode active material particles, and an SEM photograph of a mixture containing the oxidation treated carbon of Reference Example 1 and electrode active material particles. It can be seen from Fig. 1 that neither the oxidation treated carbon of Example 1 nor the oxidation treated carbon of Reference Example 1 has a granular shape, and the oxidation treated carbon that has turned into a paste-like form is attached to the surfaces of the active material particles.
[0083] The presence or absence of the paste-like property of the oxidation-treated carbon obtained from the observation results of SEM photographs is summarized in Table 1. In Table 1, when a photograph was taken showing a state in which the oxidation-treated carbon that had turned into a paste was attached to the surface of an electrode active material particle, an "O" is given, and when a photograph was taken showing a state in which granular oxidation-treated carbon was attached to the surface of an electrode active material particle, an "X" is given.
[0084] [Table 1]
[0085] As can be seen from Table 1, i) the internal specific surface area is 30 m 2 By selecting carbon as the carbon raw material that satisfies all of the following conditions: ii) average primary particle size is 35 nm or less; iii) ratio of peak intensity of S1 band to peak intensity of S2 band in Raman spectrum is 1.00 or less, oxidation treated carbon having a property of changing into a paste-like form when pressure is applied can be obtained by oxidation treatment intensity equivalent to that applied to Ketjen Black. Note that the content of hydrophilic moieties in the oxidation treated carbon in Examples 1 to 5 and Reference Example 1 exceeded 10 mass% of the entire oxidation treated carbon, but the content of hydrophilic moieties in the oxidation treated carbon in Comparative Examples 1 to 3 was less than 10 mass% of the entire oxidation treated carbon, and oxidation treated carbon having hydrophilic moieties of 10 mass% or more of the entire oxidation treated carbon had the property of easily spreading into a paste-like form when pressure is applied.
[0086] (2) Manufacturing of carbon mixtures and pellets (electrodes) (a) Preparation of pellets containing solid electrolyte particles A carbon mixture was obtained using any of the oxidized carbons of Examples 1 to 5, Comparative Examples 1 to 3, and Reference Example 1, and pellets containing the obtained carbon mixture, electrode active material particles, and solid electrolyte particles were formed, and the pellet densities were compared.
[0087] (a-1) Dry mixing using divided solid electrolyte particles Example 6 The oxidized carbon of Example 1 was introduced into a vibration ball mill and ground for 20 minutes under the condition of 10 Hz. Next, the ground oxidized carbon and furnace black, another conductive carbon, with an average primary particle size of 25 nm were introduced into the vibration ball mill in a mass ratio of 1:1 and dry mixed for 10 minutes at 20 Hz to obtain a carbon mixture. Next, 2 parts by mass of the carbon mixture and 15 parts by mass of particles of 75 mol% Li2S-25 mol% P2S5 as a solid electrolyte were introduced into a mortar and dry mixed for 5 minutes (first step), and further, commercially available LiNi 0.5 Mn 0.3 Co 0.2 68 parts by mass of O2 particles (average particle size 5 μm) were introduced and dry mixed for 5 minutes (second step), and 15 parts by mass of 75 mol% Li2S-25 mol% P2S5 particles as a solid electrolyte were introduced and dry mixed for 5 minutes (third step) to obtain an electrode mixture. Next, a powder resistivity measurement system (MCP-PD51, manufactured by Mitsubishi Chemical Analytical) was used to dry press 2.3 g of the obtained electrode mixture at a pressure of 63 MPa to produce pellets, and the pellet density was calculated from the volume of the obtained pellets.
[0088] Example 7 The procedure set forth in Example 6 was repeated, except that the oxidation treated carbon of Example 2 was used instead of the oxidation treated carbon of Example 1.
[0089] Example 8 The procedure set forth in Example 6 was repeated, except that the oxidation treated carbon of Example 3 was used instead of the oxidation treated carbon of Example 1.
[0090] Example 9 The procedure set forth in Example 6 was repeated, except that the oxidation treated carbon of Example 4 was used instead of the oxidation treated carbon of Example 1.
[0091] Example 10 The procedure set forth in Example 6 was repeated, except that the oxidation treated carbon of Example 5 was used instead of the oxidation treated carbon of Example 1.
[0092] Comparative Example 4 The procedure set forth in Example 6 was repeated, except that the oxidation treated carbon of Comparative Example 1 was used instead of the oxidation treated carbon of Example 1.
[0093] Comparative Example 5 The procedure set forth in Example 6 was repeated, except that the oxidation treated carbon of Example 1 was replaced by the oxidation treated carbon of Comparative Example 2.
[0094] Comparative Example 6 The procedure set forth in Example 6 was repeated, except that the oxidation treated carbon of Example 1 was replaced with the oxidation treated carbon of Comparative Example 3.
[0095] Reference example 2 The procedure set forth in Example 6 was repeated, except that the oxidation-treated carbon of Reference Example 1 was used instead of the oxidation-treated carbon of Example 1.
[0096] Table 2 summarizes the pellet densities obtained. [Table 2]
[0097] As can be seen from Table 2, the carbon raw material is: i) carbon with an internal specific surface area of 30 m 2The pellets in Examples 6 to 10, which contain oxidation-treated carbon having a property of turning into a paste-like shape when subjected to pressure induced from carbon satisfying all of the following conditions: ii) average primary particle size of 35 nm or less; iii) ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in the Raman spectrum of 1.00 or less, showed a higher pellet density than the pellets in Comparative Examples 4 to 6, which contain oxidation-treated carbon not having the property of turning into a paste-like shape when subjected to pressure induced from carbon not satisfying any of the above conditions i), ii), and iii). Furthermore, the pellets in Reference Example 2, which contain oxidation-treated carbon derived from Ketjen Black, showed a lower pellet density than the pellets in Examples 1 to 5, even though this oxidation-treated carbon has the property of turning into a paste-like shape when subjected to pressure.
[0098] 2 shows SEM photographs of the cross section of the pellet of Example 7 containing the oxidized carbon of Example 2, and SEM photographs of the cross section of the pellet of Comparative Example 6 containing the oxidized carbon of Comparative Example 3. Many voids surrounded by dashed lines were generated inside the pellet of Comparative Example 6, and it was determined that these voids reduced the pellet density. In contrast, the generation of voids was significantly suppressed inside the pellet of Example 7.
[0099] (a-2) Comparison with dry mixing using the entire amount of solid electrolyte Example 11 Commercially available LiNi as electrode active material 0.5 Mn 0.3 Co 0.298 parts by mass of O2 particles (average particle size 5 μm), 2 parts by mass of the carbon mixture in Example 7 containing the oxidized carbon of Example 2, and 30 parts by mass of 75 mol% Li2S-25 mol% P2S5 particles as a solid electrolyte were introduced into a planetary centrifugal mixer (product name: Awatori Rentaro, manufactured by Thinky Corporation), and dry-mixed at 2000 rpm for 5 minutes to obtain an electrode mixture. Next, a powder resistivity measurement system (MCP-PD51, manufactured by Mitsubishi Chemical Analytical) was used to dry-press 2.3 g of the obtained electrode mixture at a pressure of 63 MPa to produce pellets, and the pellet density was calculated from the volume of the obtained pellets.
[0100] The density of the pellet in Example 11 was 3.0 g / cc, which was lower than the density of the pellet in Example 7, which was 3.4 g / cc, in which dry mixing including the first to third steps was performed. Therefore, it was found that the method of performing dry mixing including the first to third steps is superior in terms of providing a high electrode density.
[0101] (b) Manufacturing of pellets that do not contain solid electrolyte Pellets were formed containing either the carbon mixtures in Examples 6 to 10 containing the oxidized carbons in Examples 1 to 5 which lead to high electrode density, or the carbon mixture in Reference Example 2 containing the oxidized carbon in Reference Example 1 derived from Ketjen Black, and electrode active material particles, and the pellet densities were compared.
[0102] Example 12 The carbon mixture in Example 6 containing the oxidized carbon of Example 1 and a commercially available LiNi 0.5 Mn 0.3 Co 0.2 The mixture for electrodes was obtained by mixing the O2 particles (average particle size 5 μm) and the O2 particles in a mass ratio of 98:2 in a mortar. Next, a powder resistance measurement system (MCP-PD51, manufactured by Mitsubishi Chemical Analytical) was used to dry press 2.3 g of the mixture for electrodes obtained, applying a pressure of 63 MPa to the mixture to produce pellets, and the pellet density was calculated from the volume of the pellets obtained.
[0103] Example 13 The procedure of Example 12 was repeated, except that the carbon mixture of Example 6 was replaced with the carbon mixture of Example 7 containing the oxidized carbon of Example 2.
[0104] Example 14 The procedure of Example 12 was repeated, except that the carbon mixture of Example 6 was replaced with the carbon mixture of Example 8 containing the oxidized carbon of Example 3.
[0105] Example 15 The procedure of Example 12 was repeated, except that the carbon mixture of Example 6 was replaced with the carbon mixture of Example 9 containing the oxidized carbon of Example 4.
[0106] Example 16 The procedure of Example 12 was repeated, except that the carbon mixture of Example 6 was replaced with the carbon mixture of Example 10 containing the oxidized carbon of Example 5.
[0107] Reference example 3 The procedure of Example 12 was repeated, except that the carbon mixture in Example 6 was replaced with the carbon mixture in Reference Example 2, which contained the oxidized carbon of Reference Example 1.
[0108] Table 3 summarizes the pellet densities obtained. [Table 3]
[0109] As can be seen from Table 3, the carbon raw material is: i) carbon with an internal specific surface area of 30 m 2The pellets in Examples 12 to 16, which contained oxidation-treated carbon having the property of turning into a paste-like shape when subjected to pressure induced from carbon that satisfies all of the following conditions: ii) an average primary particle size of 35 nm or less; and iii) a ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in a Raman spectrum of 1.00 or less, showed a higher pellet density than the pellets in Reference Example 3, which contained oxidation-treated carbon having the property of turning into a paste-like shape when subjected to pressure induced from Ketjen black. [Industrial Applicability]
[0110] The oxidized carbon obtained by the production method of the present invention and a carbon mixture containing the oxidized carbon can be used to produce an electrode for an electricity storage device having high electrode density via a dry process.
Claims
1. A method for producing oxidized carbon to be used as a conductive agent in an electrode of an electricity storage device, comprising the steps of: The oxidation step is to obtain oxidized carbon that has the property of turning into a paste when subjected to pressure by subjecting a conductive carbon raw material to an oxidation treatment. Including, The carbon raw material satisfies the following conditions i), ii) and iii): i) Internal specific surface area is 30 m 2 / g or less, ii) the average primary particle size is 35 nm or less; iii) the ratio of the peak intensity of the S1 band to the peak intensity of the S2 band in a Raman spectrum is 1.00 or less; The present invention relates to a method for producing an oxidized carbon, the method being characterized in that the carbon satisfies all of the above requirements.
2. 2. The method for producing oxidized carbon according to claim 1, wherein in the oxidation step, the oxidation is carried out so that the content of hydrophilic portions in the obtained oxidized carbon is 10 mass % or more of the total oxidized carbon.
3. A method for producing a carbon mixture to be used as a conductive agent in an electrode of an electrical storage device, comprising the steps of: A mixing step of dry-mixing the oxidized carbon obtained by the manufacturing method according to claim 1 or 2 with another conductive carbon having a higher conductivity than that of the oxidized carbon to obtain a carbon mixture in which at least a part of the oxidized carbon spreads in a paste-like form and adheres to the surface of the other conductive carbon. A method for producing a carbon mixture, comprising:
4. The carbon mixture obtained in the mixing step is heat-treated in a vacuum or a non-oxidizing atmosphere, thereby reducing the amount of CO generated from the heat-treated carbon mixture in the range of 25 to 200°C. 2 The amount of CO generated from the carbon mixture before heat treatment at temperatures between 25 and 200°C 2 Reduce the amount by heat treatment The method for producing the carbon mixture of claim 3 further comprising:
5. A method for manufacturing an electrode of an electricity storage device, comprising the steps of: a dry mixing step of dry-mixing electrode active material particles with the oxidation-treated carbon obtained by the manufacturing method according to claim 1 or 2 to obtain an electrode mixture in which at least a part of the oxidation-treated carbon spreads in a paste-like form and adheres to the surfaces of the electrode active material particles; and A dry pressing process is performed on the electrode mixture to obtain an electrode in which the oxidized carbon is further spread in a paste-like form and densified. A method for producing an electrode, comprising:
6. A method for manufacturing an electrode of an electricity storage device, comprising the steps of: a dry mixing step of dry-mixing electrode active material particles with a carbon mixture obtained by the manufacturing method according to claim 3 to obtain an electrode mixture in which at least a part of the carbon originating from the oxidized carbon spreads in a paste-like form and adheres not only to the surface of the separate conductive carbon but also to the surface of the electrode active material particles; and A dry pressing process is performed on the electrode mixture to obtain an electrode in which at least a part of the carbon derived from the oxidized carbon, which has spread in a paste-like form, further spreads in a paste-like form and becomes densified. A method for producing an electrode, comprising:
7. the electricity storage device is an all-solid-state battery having an electrolyte layer made of an inorganic solid electrolyte, an organic solid electrolyte, or a gel electrolyte; 7. The method for producing an electrode according to claim 6, wherein in the dry mixing step, solid electrolyte particles for forming an ion conduction path between the electrolyte layer and the electrode active material particles are dry mixed in addition to the electrode active material particles and the carbon mixture to obtain a mixture for an electrode.
8. The dry mixing step comprises: A first step of dry-mixing the carbon mixture with a portion of the solid electrolyte particles used for the electrode mixture; A second step of dry-mixing the mixture obtained in the first step with the electrode active material particles; and A third step of dry-mixing the mixture obtained in the second step with the remaining solid electrolyte particles to obtain a mixture for an electrode. A method for producing the electrode of claim 7, comprising:
9. The method for producing an electrode according to claim 8 , wherein the solid electrolyte particles are particles of a sulfide-based solid electrolyte.
Citation Information
Patent Citations
Electrode, method for producing the electrode, electricity storage device provided with the electrode, and conductive carbon mixture for electricity storage device electrode
JP2016096125A
Conductive carbon and production method thereof, production method of conductive carbon mixture containing the conductive carbon, and production method of electrode by use of the conductive carbon or conductive carbon mixture
JP2022035788A
Conductive carbon, electrode material including said conductive carbon, and electrode using said electrode material
WO2015133586A1